The creation and application of a large-scale corpus-based academic multi-word unit list. (April 2021) - Rogers, James; Müller, Amanda; Daulton, Frank E.; Dickinson, Paul; Florescu, Cosmin; Reid, Gordon; Stoeckel, Tim
Abstract: This paper outlines a project involving the construction of a corpus-based list which provides a large-scale selection of multi-word units that occur in academic English. Using the most up-to-date, reliable methods, the goal was to produce a large-scale resource which could either be studied directly or used as a reference for practitioners to create further resources. The paper details the procedures used to generate this academic multi-word unit list, explains why specific decisions were made to identify useful items, and discusses the resulting resource. Comparisons will be made between the list created and currently existing lists, and also between the characteristics of the list created versus characteristics of high-frequency general English word lists. Finally, applications of this free resource for English practitioners and students will be suggested. Highlights: This paper outlines the steps in the construction of a corpus-based academic English resource list. A concgram-based methodology is used, in conjunction with manual processing of items. It provides a large set of academic multiword units for educators and learners to use. Comparisons are made about the features of this list to existing English for Academic Purposes resources. Links are made between academic English and general English.